2022
DOI: 10.3390/md20040271
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Toxins and Their Potential Therapeutic Applications: A Journey toward the Quest for Potent Pharmaceuticals

Abstract: Phytoplankton are prominent organisms that contain numerous bioactive substances and secondary metabolites, including toxins, which can be valuable to pharmaceutical, nutraceutical, and biotechnological industries. Studies on toxins produced by phytoplankton such as cyanobacteria, diatoms, and dinoflagellates have become more prevalent in recent years and have sparked much interest in this field of research. Because of their richness and complexity, they have great potential as medicinal remedies and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 217 publications
0
10
0
Order By: Relevance
“…In this regard, phytoplankton are gaining much attention [122]. Although phytoplankton toxins are poisonous to organisms, they are increasingly being investigated as a potential therapeutic for diseases including cancer, Alzheimer's disease, AIDS, diabetes, and others [123]. Oscillatoxin and its analogs from the cyanobacterium Lyngbya sp., such as oscillatoxin E and 30-methyloscillatoxin D, suppressed Kv1.5 expression in CHO cells with IC50 values of 0.79 ± 0.032 and 1.47 ± 0.138 M, respectively.…”
Section: Phytoplankton Toxin and Their Disease Preventing Activitiesmentioning
confidence: 99%
“…In this regard, phytoplankton are gaining much attention [122]. Although phytoplankton toxins are poisonous to organisms, they are increasingly being investigated as a potential therapeutic for diseases including cancer, Alzheimer's disease, AIDS, diabetes, and others [123]. Oscillatoxin and its analogs from the cyanobacterium Lyngbya sp., such as oscillatoxin E and 30-methyloscillatoxin D, suppressed Kv1.5 expression in CHO cells with IC50 values of 0.79 ± 0.032 and 1.47 ± 0.138 M, respectively.…”
Section: Phytoplankton Toxin and Their Disease Preventing Activitiesmentioning
confidence: 99%
“…In larvae exposed to ethanol (positive control for induction of apoptosis), 39% of the cells were in late apoptosis or dead; percentage only observed for larvae exposed to 2.69 μg L −1 KmTx-2 (equivalent) at the end of the experiment. Finally, it is suggested that the karlotoxin (KmTx) mode of action is dependent on the sterol composition of the target cell membranes (Pradhan and Ki 2022). Possibly, the ability of KmTx to cause the formation of pores in cell membranes would trigger apoptosis at sublethal concentrations (below EC 50) and necrosis at greater concentrations (above EC 50) (Deeds et al 2006(Deeds et al , 2015.…”
Section: Embryotoxicity Of K Veneficum Supernatantmentioning
confidence: 99%
“…In addition to the freshwater, the marine environment is also rich in algal biodiversity (Behera et al, 2020; Dash et al, 2020; Dash et al, 2021; Pradhan & Ki, 2022). These algae possess diverse groups of naturally active therapeutic phytochemicals with anticancer, antioxidant, anti‐inflammatory, antibiotic, antiviral, and antibacterial properties (Behera et al, 2021; Maharana et al, 2019; Malve, 2016; Pradhan, Bhuyan, Patra, Nayak, Behera, et al, 2022; Pradhan & Ki, 2022; Pradhan, Kim, Abassi, & Ki, 2022; Pradhan, Maharana, Bhakta, & Jena, 2021; Pradhan, Patra, Dash, et al, 2021; Pradhan, Patra, Dash, Satapathy, Nayak, et al, 2022). Naturally active therapeutic phytochemicals include proteins, vitamins, omega‐3 fatty acids, and other antioxidant compounds, such as carotenoids, phenolics, polyphenolics, and flavonoid compounds (Mohanty et al, 2020; Pradhan, Nayak, Bhuyan, Patra, Behera, et al, 2022; Pradhan, Nayak, Patra, Bhuyan, Behera, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their nutritional benefits, seaweeds are a rich source of metabolites with bioactive (health‐promoting) properties, with over 15,000 new chemicals discovered recently (Gomez‐Zavaglia et al, 2019). In addition to the freshwater, the marine environment is also rich in algal biodiversity (Behera et al, 2020; Dash et al, 2020; Dash et al, 2021; Pradhan & Ki, 2022). These algae possess diverse groups of naturally active therapeutic phytochemicals with anticancer, antioxidant, anti‐inflammatory, antibiotic, antiviral, and antibacterial properties (Behera et al, 2021; Maharana et al, 2019; Malve, 2016; Pradhan, Bhuyan, Patra, Nayak, Behera, et al, 2022; Pradhan & Ki, 2022; Pradhan, Kim, Abassi, & Ki, 2022; Pradhan, Maharana, Bhakta, & Jena, 2021; Pradhan, Patra, Dash, et al, 2021; Pradhan, Patra, Dash, Satapathy, Nayak, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%